2019
DOI: 10.2139/ssrn.3451332
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Air Pollution on Migration: Evidence from China

Abstract: We thank Jianghao Wang for providing excellent research assistance. Any remaining errors are our own. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 39 publications
4
70
0
Order By: Relevance
“…To ensure that our instrument meets the exclusion restriction criteria, we control for flexible weather variables so that thermal inversions affect body weight only through air pollution. Thermal inversions have been used as IV for air pollution in several studies, including Hicks et al (2015), Arceo et al, (2016), Chen et al (2017), Fu et al, (2017), Chen et al (2018), and Jans et al (2018).…”
Section: Empirical Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure that our instrument meets the exclusion restriction criteria, we control for flexible weather variables so that thermal inversions affect body weight only through air pollution. Thermal inversions have been used as IV for air pollution in several studies, including Hicks et al (2015), Arceo et al, (2016), Chen et al (2017), Fu et al, (2017), Chen et al (2018), and Jans et al (2018).…”
Section: Empirical Strategymentioning
confidence: 99%
“…further average to the 12-month exposure window. This dataset has been used in previous studies (Chen et al, 2017;Fu et al, 2017), and validated with ground-based pollution data in China (Chen et al, 2017). We do not use ground-based pollution data mainly because they are only available after 2000 and covered only a few cities.…”
Section: Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bayer et al (2009) used a hedonic method to estimate the effect of clean air as an amenity, and found that air quality could influence long-term migration. At the sub-national level, degradation of air quality from 1996 to 2010 has significantly decreased migration inflows in Chinese counties (Chen et al 2017). However, few studies have discussed the impact of air quality on short-term population mobility, especially in developing countries such as China where air pollution tends to be more severe.…”
Section: Introductionmentioning
confidence: 99%
“…As will be discussed in Section 2, studies show that one of the main adverse impacts of a deteriorating environment is the impediment of labor flow. Poor environmental amenity quality could deter professional workers from migrating to a city [7], and is also associated with a city's emigration rate [8][9][10]. Such pull and push forces could together induce a substantial loss of human capital for the economy with deteriorating environmental quality.…”
Section: Introductionmentioning
confidence: 99%